2006
DOI: 10.1144/1470-9236/05-020
|View full text |Cite
|
Sign up to set email alerts
|

Landslides in the Alaknanda Valley of Garhwal Himalaya, India

Abstract: The occurrence of landslides is a recurring problem along the hill roads of Himalaya. Roads are often blocked due to landslides, which sometimes also leads to casualties. Identification of such unstable slopes is an imperative task to save life and property. The paper outlines features of major landslides along a National Highway in the Alaknanda valley of Garhwal Himalaya through photo documentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…5 implied that all the maximum rainfall events without landslides in the test period between 1992 and 2009 were plotted well below the threshold line indicating that 30 days antecedent period is more effective in predicting the landslides in this region. The threshold was validated using the threat score [9,27,28]. The Threat Score (TS) is calculated as the ratio between the True Positives (where landslides have occurred when the threshold was exceeded) and the sum of True Positives (TP), False Negative (where landslides have occurred when the threshold was not exceeded) and False Positive (where landslides have not occurred though threshold was exceeded).…”
Section: Validationmentioning
confidence: 99%
“…5 implied that all the maximum rainfall events without landslides in the test period between 1992 and 2009 were plotted well below the threshold line indicating that 30 days antecedent period is more effective in predicting the landslides in this region. The threshold was validated using the threat score [9,27,28]. The Threat Score (TS) is calculated as the ratio between the True Positives (where landslides have occurred when the threshold was exceeded) and the sum of True Positives (TP), False Negative (where landslides have occurred when the threshold was not exceeded) and False Positive (where landslides have not occurred though threshold was exceeded).…”
Section: Validationmentioning
confidence: 99%
“…Many workers have carried out the studies of landslides in different part of Garhwal and Kumaun regions of Uttarakhand using various methods and techniques [40][41][42][43][44][45]. A landslide inventory is an important database extent and amount of landslide occurrences [46].…”
Section: Landslide Incidencesmentioning
confidence: 99%
“…In the Indian Himalayan Region (IHR), landslide frequently occurs due to internal factors such as lithology setting, higher altitude, steep slope, fragile soil, high relief, and groundwater. However, the previous studies also emphasize that external factors such as heavy rainfall, earthquakes, and anthropogenic activities such as deforestation, shifting agriculture, road construction, and agriculture expansion further increased landslides in many potentially unstable slope areas [22][23][24][25][26]. The recently updated global landslide catalog (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018) available on NASA's open data portal (https://data.nasa.gov/browse (accessed on 2 August 2020)) indicated that the Indian Himalayas is a hotspot area of landslides that were mainly triggered by rainfall.…”
Section: Introductionmentioning
confidence: 99%